Minat Siswa SMKN di Kota Padang Melanjutkan KeProgram Studi Tata Rias Dan KecantikanFakultas Pariwisata Dan Perhotelan Universitas Negeri Padang - Ningrum, Mercylia; Rostamailis, Rostamailis; Hayatunnufus, Hayatunnufus (Journal of Home Economics and Tourism, 2016)
The background of this research is because the existence of phenomena that shows the low interests of Vocational High School students who majoring in Make Up and Beauty to continue their education to Make Up and Beauty Major of Tourism and Hospitality Faculty in Padang State University. This research aims to describe the interests of the students of Vocational High School Number 6 and 7 in Padang who continue their education to Make Up and Beauty Major of Tourism and Hospitality Faculty in Padang State University. This research aims to describe the interests of the students of Vocational High School Number 6 and 7 in Padang who continue their education to Make Up and Beauty Major of Tourism and Hospitality Faculty in Padang State University, viewed from the internal and external factors. The population of this research is all the students on XI and XII grade of Vocational High School number 6 dan 7 in Padang in the academic year 2015-2016 with the total 172 students. While a sampel study is in total 63 students by using proportional random sampling.The result of the research show the average of respondents achievement (TPR) of interest of Public Vocational High School students in Padang in continuing to Make Up and Beauty Major of Tourism and Hospitality Faculty in Padang State University viewed from internal factor has 59,73% in percentage which is categorized low. The external indicator has 63,30% percentage which is categorized low.According to the research results. It is suggested for Make Up and Beauty Major to pay more attention on students interest by providing information to the Vocational High School students in the form prospects and career opportunities they will have after graduation.Keywords : Student Interests ( Internal and External Factors).